The digitization of cassette archives in the House of Representatives of the Republic Indonesia - Najwa Nabila (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Archives are recordings of information with historical, administrative, and legal value that must be preserved to maintain the sustainability of information. In the House of Representatives of the Republic of Indonesia, cassette archives containing meeting recordings hold significant value as inactive dynamic documents that require proper management. The media transfer of archives, especially from analog cassettes to digital formats, is an effective solution to increase accessibility, extend the lifespan of archives, and promote transparency within legislative institutions. This service employs a mentoring method conducted by practitioners, after which the practical results are analyzed following regulations governing media transfer and research on related topics. The service results indicate that the primary challenges in media transfer are technological limitations, physical degradation of cassettes, and a lack of understanding of standards and regulations among employees. The proposed solutions include investing in modern technology, conducting routine physical maintenance of cassettes, and training employees to understand the guidelines for transferring archive media. Proper implementation of this process supports the preservation of archives and facilitates access to information for various parties so that archives remain relevant and valuable in the digital era.   Abstrak Arsip merupakan rekaman informasi yang memiliki nilai historis, administratif, dan legal yang perlu dilestarikan untuk menjaga keberlangsungan informasi. Dalam konteks Dewan Perwakilan Rakyat (DPR) Republik Indonesia, arsip kaset yang berisi rekaman rapat memiliki nilai penting sebagai dokumen dinamis inaktif yang harus dikelola dengan baik. Alih media arsip, terutama dari kaset analog ke format digital, menjadi solusi efektif untuk meningkatkan aksesibilitas, memperpanjang umur arsip, dan mendukung transparansi lembaga legislatif. Pengabdian ini menggunakan metode mentoring yang dilakukan oleh praktisi, kemudian hasil praktis yang dilakukan dianalisis berdasarkan peraturan-peraturan mengenai alih media dan penelitian dengan topik terkait. Hasil pengabdian menunjukkan bahwa tantangan utama dalam alih media adalah keterbatasan teknologi, degradasi fisik kaset, serta kurangnya pemahaman standar dan regulasi oleh pegawai. Solusi yang diusulkan meliputi investasi teknologi modern, perawatan fisik kaset secara rutin, serta pelatihan pegawai untuk memahami pedoman alih media arsip. Implementasi yang tepat terhadap proses ini mendukung pelestarian arsip dan mempermudah akses informasi bagi berbagai pihak, sehingga arsip tetap relevan dan bermanfaat di era digital. Kata Kunci: alih media arsip; arsip kaset, digitalisasi; pengelolaan arsip